Factors Contributing to High Employee Turnover of Lawyers in Law Firms in Kenya - Maangi, Josephine; Wambalaba, Francis (Journal of Modern Law and Policy, 2017)
Purpose: The purpose of this study was to determine the factors contributing to high employee turnover of lawyers in law firms in Kenya. Methodology: The research design was descriptive survey design. The population of the study was all practicing lawyers based in Nairobi County. The target population is over ten thousand (10,000) lawyers in Nairobi County. The sampling frame was lawyers who are members of LSK. Data was analyzed using Statistical Package for Social Sciences (SPSS) and results were presented in frequency tables. Data was analyzed using Statistical Package for Social Sciences (SPSS) and results presented in frequency tables. The data was then analyzed in terms of descriptive statistics like frequencies, means and percentages. Results: The study results show that employee turnover was highly emphasized in law firms. The results of the study showed that effects of employee turnover were highly emphasized in law firms. Unique Contribution to Theory, Practice and Policy: The study recommended that Management should improve the terms and conditions of services to improve on the employee retention rate so as to avoid liabilities caused by staff turnover and they should provide good working conditions and being transparent and fair to their employee